Development and assessment of a device and method for studying the mechanical interactions between shoes and playing surfaces in situ at loads and rates generated by elite athletes - Kent, R.; Crandall, J.; Forman, J.; Lessley, D.; Lau, A.; Garson, C. (Sports Biomechanics, 2012)
The literature is lacking the description of a device and method for simulating and measuring shoe-turf interactions at loads and rates generated in situ by elite athletes during performance. A transportable device was built to quantify these interactions through three tests that reflect generic classes of tasks: 1) translation test; 2) rotation test; and 3) translation/drop test. All the three tests were performed using the cleated portion of a molded American football shoe on two types of natural grass surfaces. To assess repeatability of tests, we performed multiple trials of each test under the same testing conditions. To assess sensitivity of the device, the type of playing surface, temperature, and moisture level were varied. The variation among the results of repeated trials of a given set of testing conditions was less than that between the results of a given test under differing testing conditions, so the device and method were deemed to have acceptable levels of repeatability and sensitivity in the set of conditions considered.